FATTY ACID COMPOSITION OF BLOOD SERUM IN CHILDREN WITH VITAMIN D-DEFICIENCY RICKETIS - Ibatova Sh. M.; Rakhmonov Yu. A. (American Journals, 2024)
Rickets still occupies an important place in the structure of morbidity in young children and remains an urgent problem in pediatrics. The disease has a negative impact on the reactivity of the body, the course and outcome of somatic diseases. The purpose of the study was to study lipid metabolism in children with rickets. We examined 47 patients receiving traditional therapy. Of these, 11 children had rickets, 15 children had rickets due to pneumonia, and 21 children had rickets due to pneumonia and malnutrition. In children suffering from rickets due to pneumonia and malnutrition, after the traditional method of treatment, there was no normalization of phosphorus-calcium metabolism and some indicators of lipid metabolism. Along with clinical recovery, total blood and fecal lipids retained increased alkaline phosphatase activity, and calcium and phosphorus levels were below normal, which indicates “incomplete recovery” and, apparently, requires further correction of biochemical parameters.
Keywords: Rickets, vitamin D, patients, fatty acids, lipid metabolism, treatment.